P5. Virtual lesion model to investigate dysphagia resulting from pharyngeal hypesthesia in healthy volunteers. Issue 8 (August 2018) - Muhle, P.; Claus, I.; Marian, T.; Schröder, J.B.; Wollbrink, A.; Pantev, C.; Warnecke, T.; Dziewas, R.; Suntrup-Krueger, S.
Abstract : Objective: Dysphagia is a frequent and outcome-relevant complication of various neurological disorders, whose treatment options are still limited. Lately, neuromodulatory treatment devices have come into focus to enhance adaptive plasticity in the cortical swallowing network. However, performing neurophysiological and functional imaging studies to investigate these novel neurostimulation techniques for the treatment of neurogenic dysphagia in severely affected patients is difficult. Therefore, basic research needs to be conducted in healthy subjects instead. Here, we propose a virtual peripheral sensory lesion model to mimic pharyngeal sensory impairment, which is known to be a major contributor to dysphagia in neurological disease, as swallowing is a motor function highly dependent on sensory afferent input. Methods: In this randomized crossover study on 11 healthy volunteers, cortical activation during pneumatic pharyngeal stimulation was measured applying 275-channel magnetoencephalography (MEG) in two separate sessions, with and without pharyngeal surface anesthesia. Individual source reconstruction was performed applying a linear constraint minimum variance (LCMV-) beamformer algorithm and significant differences between conditions were assessed with a nonparametric permutation test. Results: Pneumatic pharyngeal stimulation evoked bilateral event-related desynchronization (ERD) mainly in the primary and secondary sensorimotor areas located in the caudolateral pericentral cortex, the insula, the prefrontal cortex and the supramarginal gyrus. In comparison to the no-anesthesia condition, topical pharyngeal anesthesia led to a virtual lesion in this network, indicated by a reduction of ERD in beta (13–30 Hz) and low gamma (30–60 Hz) frequency ranges ( p  < 0.05) in sensory but also motor cortical areas. Conclusions: Withdrawal of sensory afferent information by topical surface anesthesia leads to reduced response to pneumatic pharyngeal stimulation in a distributed cortical sensorimotor network in healthy subjects thereby mimicking the situation in patients with dysphagia related to sensory impairment. Significance: The proposed virtual sensory lesion paradigm may serve to investigate the effect of neuromodulatory treatments specifically on pharyngeal sensory impairment as relevant cause of neurogenic dysphagia.